Bahasa Inggris - Jihat Nurrahman; Hodairiyah Hodairiyah; Ray Suryadi (Musamus Journal of Language and Literature, 2022)
This research aimed at explaining the implementation of Student Team Achievement Division (STAD) technique in enhancing the students’ reading comprehension. The study was a classroom action research. The research was carried out in a cyclic process. The subject of this study were the students of semester I Mathematics Education Study Program STKIP PGRI Sumenep in the academic year 2022/2023. The data were collected through a number of instruments namely observation sheets and field-note analyzed qualitatively, and the result of the quizzes were analyzed quantitatively. The findings show that first, there was a significant improvement on the students’ reading achievement after being taught by using STAD Technique. Second, there was a good improvement on the students’ responsibility in learning the lesson and the students’ learning motivation. Based on the quizzes given at the end of each cycle, there was a significant improvement in the students’ reading comprehension. In the first cycle, the average score gained by the students was only 59%, in the second cycle, the average score improved at the level of 77%, and in the last cycle, the students’ average score was 88%. A conclusion can be drawn then the implementation of the STAD technique gave contribution positively in enhancing the students’ reading comprehension